KEBIJAKAN REDAKSIONAL DALAM PEMBERITAAN DI 107,5 PR FM NEWS CHANNEL - Dudi Yudhakusuma (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Radio PRFM is one of the radio news in the city who is also a member of the general daily newspaper Harlan that have programs Citizen Report with the concept of Citizen Journalism broadcast over channel FM 107.5. With the concept of Citizen Journalism is so thick provides the widest space for the participation of the public in delivering an information, the editorial of the special strategy is required to filter the information that goes into the radio news. The research is a qualitative study using descriptive methods. The focus of research is how the editorial policy in reporting on the event program Citizen Report at 107.5 PRFM News Channel. The result showed bahwasannya in editorial policy consists of internal and external policies, internal policies include: policy decision-making in the news, news production policy, as well as journalistic ethics policy. External policy includes criteria that must be met by the residents. Besides influencing editorial policy report form coverage of the citizens in the form of photograph or video, sms, phone, and social media PRFM are also delivered through group Netizen Photo PRFM. Editorial policy also affects the form of citizen journalism that is applied to a radio station, as well as affect the feel of the news in the event, it is due to the filtering process of a team of editors and their agenda setting with an emphasis on certain issues visible on the theme or news broadcast.